Inclusiveness of Iqbal’s educational thought. - Ali, Muhammad Abid; Hussien, Suhailah (Islamic Research Centre Bahauddin Zakariya Universitry Multan, Pakistan, 2016)
The contemporary education system, though grooming the youth for running economy and industries, is severely inhibiting the creativity in children.It is based on the ‘Factory model of education’ and not compatible with a child’s learning faculties as put by Sir Ken Robinson, in his TED Talk in 2010. When we look from our own perspective, in addition it is also acutely diminishing the vital spiritual aspect in children. With all the above weaknesses it cannot serve the purpose of grooming the youth of Muslim ummah to take their position as Khalifa of Allah subhanawata’ala. Has Iqbal given us clear directives for an education system from Islamic perspective? My research findings are that he has, which we can discover in his two Persian anthologies of Asrar i khudi (Secrets of the Self), and Ramooz i bikhudi (Mysteries of Selflessness).And that these directives are quite inclusive to design an education system from an Islamic perspective. Iqbal was selected for my project, as he is considered to be the ideologue of Pakistan and has lucidly presented his educational philosophy. Exploring Iqbal’s educational thought includes drawing hermeneutical interpretations from Asrar i khudi (Secrets of the Self), and Ramooz i bikhudi (Mysteries of Selflessness). Thematic data analysis was used to draw the aims and objectives for education from Iqbal’s said works. This paper attempts to explore the inclusiveness of Iqbal’s educational directives from the perspective of developing an Islamic education model.